Can an hour or two of sun protection education keep the sunburn away? Evaluation of the Environmental Protection Agency's Sunwise School Program - Kenausis Kristin; Rutsch Linda; Geller Alan C; Selzer Paula; Zhang Zi (BMC, 2003)
Abstract Background Melanoma incidence is rising at a rate faster than any other preventable cancer in the United States. Childhood exposure to ultraviolet (UV) light increases risk for skin cancer as an adult, thus starting positive sun protection habits early may be key to reducing the incidence of this disease. Methods The Environmental Protection Agency's SunWise School Program, a national environmental and health education program for sun safety of children in primary and secondary schools (grades K-8), was evaluated with surveys administered to participating students and faculty. Results Pretests (n = 5,625) and posttests (n = 5,028) were completed by students in 102 schools in 42 states. Significant improvement was noted for the three knowledge variables. Intentions to play in the shade increased from 68% to 75%(p < 0.001) with more modest changes in intentions to use sunscreen. Attitudes regarding healthiness of a tan also decreased significantly. Conclusions Brief, standardized sun protection education can be efficiently interwoven into existing school curricula, and result in improvements in knowledge and positive intentions for sun protection.